Bemerkungen zu einigen Lamiiden des Deutschen Entomologischen Instituts (Coleoptera: Cerambycidae). - Breuning, Stephan von (Contributions to Entomology = Beiträge zur Entomologie, 1958)
Based upon the material of Cerambycidae in the collection of the Deutsches Entomologisches Institut there are described: a new genus (Mimatimura), a new subgenus (Crassapomecyna), a new species (Glenea bipunetithorax), and a new subspecies (Glenea laterinuda quadrivitticollis). Nomenclatural Acts Mimatimura Breuning, 1958 (Cerambycidae), gen. n. bipunctithorax Breuning, 1958 (Glenea (Glenea)), spec. n. quadrivitticollis Breuning, 1958 (Glenea (Glenea) laterinuda), sspec. n.